Peran Orang Tua terhadap Perilaku Kedisiplinan Anak di Kelas 4 Sekolah Dasar SDN Dukuh 04 Pagi - Nadia Safitri; Kasriman Kasriman (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
This research aims to identify the most effective parenting strategies in shaping children's discipline and determine the extent to which parental roles influence children's disciplinary behavior in elementary schools, specifically in grade 4 at SDN Dukuh 04 Pagi. The research method used is quantitative, with a population of 97 grade 4 students and a sample of 35 students selected through proportionate stratified random sampling. Data were collected through observation and questionnaires and then analyzed using simple linear regression. The research results show that parental roles have a significant influence on children's disciplinary behavior, with an R Square value of 37.2%, indicating that the parental role variable explains 37.2% of the variation in children's disciplinary behavior, while 62.8% is influenced by other factors. This study concludes that parental roles have a significant impact on the disciplinary behavior of grade 4 students at SDN Dukuh 04 Pagi. Parents who actively support household rules, provide positive guidance, and give adequate time and attention significantly contribute to the formation of children's discipline. Given the importance of this role, it is recommended that schools collaborate with parents to strengthen effective parenting strategies.